Essays on meso-institutions: evidences from the dairy sector - Oliveira, Gustavo Magalhães de (2019)
This dissertation investigates a recent development in New Institutional Economics that draws attention to the division of three institutional layers - macro, meso and micro. I present an analysis considering the systematic connection between these layers and also a particular investigation of the meso-level. Using historical secondary data on milk regulations in Brazil and Italy, and a fine-grained dataset related to daily laboratory analysis of cow milk quality from 25 of the 27 Brazilian states during a nineteen-year period (1999-2017), I address some research questions in the fields of institutional economics, strategic management and food policy. This dissertation includes three individual chapters in the format of academic articles, besides a general introduction and conclusion. Chapter 2 focuses on the field of institutional economics by addressing the gap in the literature in providing a systematic approach detailing the relationships between macro, meso and micro institutional layers and their analysis as a system. This part presents three concepts - institutional interconnectivity, institutional complementarity, institutional alignment - to enrich this new debate. I adopt a historical and regulatory perspective to employ these concepts in the dairy industry in Brazil and Italy. I present some propositions related to the functioning of institutional layers and their basis in terms of transaction costs. Drawing on regulatory institutional voids, Chapter 3 investigates the impact of meso-institution\'s translation effects on performance, as well as the dependence of this influence on firm-level resources. As expected, I observe the creation of a meso-institution overcoming these institutional voids and increasing firms\' performance, due to the information provision mechanisms that simplify complex rules and induce firms to achieve a better fit between their external and internal environments in terms of resource allocation. I also demonstrate the particular relevance of meso-institutions\' translation effects for small firms. Some contributions to the institutions-based strategy literature are presented. Chapter 4 brings the analysis of efficient meso-institutions affecting the effectiveness of food policy implementation. I find that the translation function of a meso-institution increases the policy\'s effectiveness and highlight a sequential logic of policy implementation from institutional (first-order) to technology and size (second-order) effects. This chapter also has policy implications, advocating that any regulation must be initially translated, and then enforced and monitored, to succeed.